Preschoolers' responses to prosocial opportunities during naturalistic interactions with peers: A cross‐cultural comparison. Issue 1 (20th June 2022) - Tavassoli, Nasim; Dunfield, Kristen; Kleis, Astrid; Recchia, Holly; Conto, Laura Pareja
Abstract: The goal of this study was to better understand similarities and differences in preschool children's expression of needs and prosocial responsiveness to peers' needs across two culturally distinct contexts. Preschoolers were observed in a semi‐naturalistic design across rural Mexico and urban Canada, wherein they were instructed to build a tower with blocks. Three‐ to 6‐year‐olds ( N = 306; 48% female) were divided into 64 peer groups. We coded for children's expression of needs (instrumental, material, or emotional), responses to prosocial opportunities (prosociality, denial, or no response), prosociality without an apparent need (spontaneous prosociality), and types of prosocial behavior (helping, sharing, or comforting). While instrumental and material needs were expressed similarly across both samples, Tzotzil Maya children expressed fewer emotional needs than Canadian children. Failing to respond to others' needs, followed by denial, were the most frequent need‐provoked response in both countries; surprisingly, only 9% of needs received a prosocial response. Though need‐provoked prosociality was rare in both cultural contexts, children engaged in considerable spontaneous prosociality which varied as a function of age, gender, and cultural context. Lastly, Canadian more than Tzotzil Maya children denied emotional and instrumental needs (but not material needs). The findings inform how cultural practices may shape the presentation of needs and prosocial responsiveness in peer interactions.